Khirqah in Sufi Traditions: Hadith-Based Legitimacy and Its Spiritual Transmission - AB, Zuherni. (El-Sunan: Journal of Hadith and Religious Studies, 2024)
The khirqah is a significant element in Sufi traditions, symbolizing spiritual initiation and the transmission of esoteric knowledge. However, its origins remain debated, particularly regarding its connection to the Prophet Muhammad (PBUH) through Imam ‘Ali and Hasan al-Basri. Some scholars affirm this lineage, while others argue that khirqah was a later development within Sufi circles rather than a direct prophetic practice. This study employs a qualitative approach, analyzing classical Sufi literature, historical records, and hadith collections. Key hadith narrations related to the bestowal of garments, such as the Prophet (PBUH) clothing Ummu Khalid and Uwais al-Qarni receiving robes from Imam ‘Ali and Umar ibn al-Khattab, have been used to validate khirqah’s legitimacy. However, critics contend that these narrations reflect acts of generosity rather than structured initiatic bestowals. By the 14th century, khirqah evolved beyond a physical robe into a symbol of spiritual affiliation within Sufi orders (tariqas). Despite these debates, khirqah remains central to Sufi identity, signifying spiritual authority, ethical discipline, and lineage transmission. Scholars such as Ibn ‘Arabi emphasized that khirqah represents inner purification rather than merely an external garment.